Impact of Chinese Herbal Medicine on Glucolipid Metabolic Outcomes in Women with Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis. (30th September 2022) - Li, Jie; Zheng, Ruqun; Lin, Zixin; Hu, Fangyuan; Lin, Ying; Zeng, Guomei; Fang, Jieni; Shen, Yingyan; Tan, Huiyan; Han, Mei; Li, Juan
Abstract : Objective . This investigation was conducted to analyze and evaluate the impact of Chinese herbal medicine on glucolipid metabolism in women with polycystic ovary syndrome (PCOS). Methods . We used manual and computer-aided search methods, and the search scopes included Chinese databases (China National Knowledge Infrastructure, Wanfang, the China Science and Technology Journal Database, and the Chinese Biomedical Literature Database) and English databases (PubMed, Embase, Web of Science, and the Cochrane Library). We searched these eight databases for randomized controlled trials investigating the effects of Chinese herbal medicine on glucolipid metabolism in women with PCOS, with the retrieval deadline being June 2021. Two reviewers screened, selected, and extracted data and verified the results independently. The NoteExpress software was used to manage and screen the literature, the risk of bias assessment tool was used to evaluate the methodological quality of the included studies, and the RevMan 5.4 software was used for meta-analysis. Results . A total of 13 trials were included, including 825 patients with PCOS. Because the drugs used in the control group were different, we divided the results into two parts, with four trials using placebo and nine trials using metformin as the control. The results of the meta-analysis showed that fasting insulin (MD = −2.45, 95% CI = [−4.74, −0.17], P = 0.04), 2 h fasting plasma glucose (MD = −0.33, 95% CI = [−0.64, −0.02], P = 0.04), serum total cholesterol (MD = −0.38, 95% CI = [−0.58, −0.18], P = 0.0002), triglycerides (MD = −0.36, 95% CI = [−0.58, −0.14], P = 0.001), and low-density lipoprotein cholesterol (MD = −0.58, 95% CI = [−0.75, −0.41], P < 0.00001) were significantly improved in the Chinese herbal medicine group compared with the placebo group. In addition, compared with metformin, body mass index (MD = −1.04, 95% CI = [−1.55, −0.53], P < 0.0001), serum total cholesterol (MD = −0.27, 95% CI = [−0.46, −0.07] P = 0.007), and low-density lipoprotein cholesterol were significantly reduced (MD = −0.12, 95% CI = [−0.22, −0.02], P = 0.02) and high-density lipoprotein cholesterol (MD = 0.09, 95% CI = [0.02, 0.17], P = 0.01) was significantly improved after treatment with Chinese herbal medicine. Conclusion . Compared with the placebo group, Chinese herbal medicine had positive effects on glucolipid metabolism in women with PCOS. Chinese herbal medicine had a positive effect on lipid metabolism when the control group was metformin, but no effect on glucose metabolism. These findings need to be verified in high-quality, large-sample, randomized controlled trials in the future.